Host guest chemistry and supramolecular doping in triphenylamine-based covalent frameworks on Au(111). Issue 21 (24th May 2021) - Steiner, Christian; Fromm, Lukas; Gebhardt, Julian; Liu, Yi; Heidenreich, Alexander; Hammer, Natalie; Görling, Andreas; Kivala, Milan; Maier, Sabine
Abstract : The post-synthetic modification of covalent organic frameworks (COFs) via host–guest chemistry is an important method to tailor their electronic properties for applications. Abstract : The post-synthetic modification of covalent organic frameworks (COFs) via host–guest chemistry is an important method to tailor their electronic properties for applications. Due to the limited structural control in the assembly of two-dimensional surface-supported COFs, supramolecular networks are traditionally used at present for host–guest experiments on surfaces, which lack structural and thermal stability, however. Here, we present a combined scanning tunneling microscopy and density functional theory study to understand the host–guest interaction in triphenylamine-based covalently-linked macrocycles and networks on Au(111). These triphenylamine-based structures feature carbonyl and hydrogen functionalized pores that create preferred adsorption sites for trimesic acid (TMA) and halogen atoms. The binding of the TMA through optimized hydrogen-bond interactions is corroborated by selective adsorption positions within the pores. Band structure calculations reveal that the strong intermolecular charge transfer through the TMA bonding reduces the band gap in the triphenylamine COFs, demonstrating the concept of supramolecular doping by host–guest interactions in surface-supported COFs. Halogen atoms selectively adsorb between two carbonyl groups at Au hollow sites. The mainly dispersive interaction of the halogens with the triphenylamine COF leads to a small downshift of the bands. Most of the halogens change their adsorption position selectively upon annealing near the desorption temperature. In conclusion, we demonstrate evidence for supramolecular doping via post-synthetic modification and to track chemical reactions in confined space.